2016
DOI: 10.1002/eap.1404
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and a strongAllee effect in a cooperative outbreak insect

Abstract: Most species that are negatively impacted when their densities are low aggregate to minimize this effect. Aggregation has the potential to change how Allee effects are expressed at the population level. We studied the interplay between aggregation and Allee effects in the mountain pine beetle (Dendroctonus ponderosae Hopkins), an irruptive bark beetle that aggregates to overcome tree defenses. By cooperating to surpass a critical number of attacks per tree, the mountain pine beetle is able to breach host defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 54 publications
(117 reference statements)
1
48
0
1
Order By: Relevance
“…Body weight and wing size contribute to dispersal capacity in mountain pine beetle, and such data can potentially be useful in improving dispersal model quality (Goodsman et al ., ). Although many other factors must also be considered in the parameterization of dispersal models, we have shown that large female beetles with large wings generally have an increased dispersal capacity, flying further than smaller beetles with smaller wings; autonomous populations in dispersal models can be assigned flight capacities based on morphology observed in situ through use of samples already being collected for monitoring purposes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Body weight and wing size contribute to dispersal capacity in mountain pine beetle, and such data can potentially be useful in improving dispersal model quality (Goodsman et al ., ). Although many other factors must also be considered in the parameterization of dispersal models, we have shown that large female beetles with large wings generally have an increased dispersal capacity, flying further than smaller beetles with smaller wings; autonomous populations in dispersal models can be assigned flight capacities based on morphology observed in situ through use of samples already being collected for monitoring purposes.…”
Section: Discussionmentioning
confidence: 97%
“…In such scenarios, equipment and manpower must be allocated in accessible areas that will maximize the impact on MPB spread at the same time as minimizing cost. Predictive modelling of MPB spread is one means of risk detection, and such models need to be parameterized with variables such as regional climate and dispersal capacity (Atkins, ; Robertson et al ., ; Aukema et al ., ; Goodsman et al ., ). Climatic data are often available, although the ability to identify MPB dispersal phenotypes is lacking.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Beetles are not able to fly indefinitely. To account for settling in beetles that expend their energy reserves for flight, we added an exponential settling function based on laboratory measurements of beetle flight propensity (Evenden, Whitehouse, & Sykes, ) and a simple model of mountain pine beetle dispersal (Goodsman et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…We do not provide a separate script containing this code as it is essentially the same as the stage-and age-structured integral projection model of mountain pine beetle demography and phenology already in the Supporting Information (Data S3). (Evenden, Whitehouse, & Sykes, 2014) and a simple model of mountain pine beetle dispersal (Goodsman et al, 2016).…”
Section: Cohort-based Mountain Pine Beetle Modelmentioning
confidence: 99%